Experimental Verification of a New Scheme of MLI Based on Modified T-Type Inverter and Switched-Diode Cell with Lower Number of Circuit Devices. Issue 16 (7th May 2021) - Mahato, Bidyut; Majumdar, Saikat; Jana, Kartick Chandra; Thakura, Parashuram; Kumar Mohanta, Dusmanta
Abstract: Multilevel inverters (MLIs) have become more popular due to the high-quality output waveform with higher voltage levels, lower voltage stress across the power switches, and lower harmonic distortion of the output voltage. This paper introduces two new structures of MLI based on a modified T-type inverter and switched-diode cell. Proposed inverter topologies cascaded in series due to its generalized structure. Inherent property to generate the negative voltage levels without using any full H-bridge circuit is a key feature of the proposed topology. The merit of the proposed inverter is the reduction in power electronic components, the assessment has been carried out with some recent MLI topologies, and graphs relating to the performance parameters have also been incorporated as well. Besides, total standing voltage (TSV) and the level to switch ratio (LSR) is calculated for further clarification of the proposed inverter, and the parameters are compared with the newly developed MLI topologies. A multi-carrier pulse width modulation strategy (MC-PWM) is adopted for the generation of the switching pulses.